Higher order thinking skills in science learning: a systematic review from 2014-2023 - Yanti, Fitri April; Thohir, M Anas (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study presents a comprehensive overview related to higher-order thinking skills (HOTs) as well as recommendations for future study opportunities for educators and researchers. This study uses the systematic literature review (SLR) method to present critically the knowledge, ideas, and findings contained in academic-oriented literature. A total of 276 synthesized papers have been selected from the Scopus database. Annual publication frequency, number of documents, research methods, scope of themes, productive journals and proceedings in research, and learning approaches used in improving HOTs are reviewed. The results show that HOTs in science education have been receiving attention from researchers in the last eight years. Based on the 63 documents reviewed, include HOTs in the title and abstract. Proceedings in the Journal of Physics: Conference Series are the most contributors to publishing HOTs in science education. Quantitative methods are more widely adopted in HOTs research than research and development (R&D), qualitative, mixed, and non-empirical methods. In addition, models of teaching are also the most chosen theme in science education, and the most widely used mobile learning approach to increase HOTs. In the future, this study can become a reference for researchers to consider various solutions to maximize HOTs.